Identifikasi Mode Kegagalan Produksi Pallet Berbahan Limbah Plastik Menggunakan Failure Mode and Effects Analysis (FMEA) di PT RII - Irman Setyawan; M. Imron Mas'ud (Jurnal Penelitian Rumpun Ilmu Teknik, 2026)
The increasing use of recycled plastic waste as an alternative raw material requires manufacturing companies to maintain process efficiency and product quality while minimizing production failures. PT RII processes plastic waste into value-added products; however, its production process still generates a considerable amount of rejected products, particularly in pallet production. This study aims to identify dominant production waste, determine the major causes of pallet production failures, and establish improvement priorities using Failure Mode and Effects Analysis (FMEA). Production data from January to June 2026, including raw material input, production output, and rejected products, were analyzed using Lean Manufacturing to identify waste, Pareto analysis to determine dominant defects, and a fishbone diagram to identify potential causes. FMEA was subsequently applied by assessing Severity, Occurrence, and Detection to establish risk priorities. The results show that defect was the dominant waste, with total rejected products reaching 215,751.8 kg, representing 12.10% of the total raw material processed. Pallet reject was the largest defect category, accounting for 43.63% of total rejected products. The highest Risk Priority Number was associated with the Method factor at 432, followed by Machine at 240, Man at 168, Material at 105, and Environment at 80. The findings imply that improvement should prioritize standardized paste arrangement procedures, operator training, preventive maintenance and machine calibration, material composition standardization, and implementation of the 5S work culture to reduce production failures and improve process efficiency and product quality.